The metabolic marker tumour pyruvate kinase type M2 (tumour M2-PK) shows increased expression along the metaplasia–dysplasia–adenocarcinoma sequence in Barrett's oesophagus. Issue 11 (27th October 2004) - Koss, K; Harrison, R F; Gregory, J; Darnton, S J; Anderson, M R; Jankowski, J A Z
Abstract : Background: Proliferating and tumour cells express the glycolytic isoenzyme, pyruvate kinase type M2 (M2-PK). In tumours cells, M2-PK usually exists in dimeric form (tumour M2-PK), causing the accumulation of glycolytic phosphometabolites, which allows cells to invade areas with low oxygen and glucose concentrations. Aims: To investigate the expression of tumour M2-PK during the metaplasia–dysplasia–adenocarcinoma sequence of Barrett's oesophagus, and to assess the prognostic usefulness of tumour M2-PK in oesophageal cancer. Materials/Methods: One hundred and ninety cases selected from the histopathology archives as follows: 17 reflux oesophagitis, 37 Barrett's oesophagus, 21 high grade dysplasia, 112 adenocarcinomas, and three control tumours. Sections were stained immunohistochemically with antibody to tumour M2-PK. Results: Tumour M2-PK was expressed in all cases, and increased cytoplasmic expression was seen with progression along the metaplasia–dysplasia–adenocarcinoma sequence. All cases of adenocarcinoma showed 100% staining so that tumour M2-PK was not a useful prognostic marker. Conclusions: Tumour M2-PK is not a specific marker of Barrett's adenocarcinoma, but may be important as a marker of transformed and highly proliferating clones during progression along the metaplasia–dysplasia–adenocarcinoma sequence.